THE EFFECTIVENESS OF VILLAGE FUND POLICY ON INFRASTRUCTURE DEVELOPMENT - Aep Saepudin; Muhammad Yusuf (Badan Penerbit STIEPARI Press, 2022)
The Effectiveness of Village Fund Policy on Infrastructure Development in Baleendah Village, Bandung Regency. This study aims to find out how effective village fund policies are in infrastructure development. This study uses a phenomenological approach with an interpretive paradigm as the research umbrella, namely an approach that describes the conditions or object of research as it happened. The results of this study indicate that the effectiveness of village funds in infrastructure development in Baleendah Village is considered appropriate. The results obtained are the right implementation, the right target, the right policy and the right environment. With the existence of a village fund policy, the Baleendah community has received and enjoyed the benefits, namely the access of the Baleendah community in everyday life is easier, the implementation is precise, that the village government of Baleendah has carried out good cooperation with the community, the city/South Bandung regency government and the private sector. Right on target, that the development carried out is in accordance with the target in the APBDes. Environmentally appropriate, that the coordination carried out by the Baleendah Village government with the community and the South Bandung city/regency government has been good, and in the external environment the mass media policy has provided information regarding developments in Rompu Village.